Evaluating the clinical dyad leadership model: a narrative review. Issue 7 (5th September 2020) - Clouser, Jessica Miller; Vundi, Nikita Leigh; Cowley, Amy Mitchell; Cook, Christopher; Williams, Mark Vincent; McIntosh, Megan; Li, Jing
Abstract : Purpose: Dyadic leadership models, in which two professionals jointly lead and share unit responsibilities, exemplifies a recent trend in health care. Nonetheless, much remains unknown about their benefits and drawbacks. In order to understand their potential impact, we conducted a review of literature evaluating dyad leadership models in health systems. Design/methodology/approach: Our narrative review began with a search of PubMed, CINAHL, Web of Science and Scopus using key terms related to dyads and leadership. The search yielded 307 articles. We screened titles/abstracts according to these criteria: (1) focus on dyadic leadership model, i.e. physician–nurse or clinician–administrator, (2) set in health care environment and (3) peer-reviewed with an evaluative component of dyadic model. This yielded 22 articles for full evaluation, of which six were relevant for this review. Findings: These six articles contribute an assessment of (1) teamwork and communication perceptions and their changes through dyad implementation, (2) dyad model functionality within the health system, (3) lessons learned from dyad model implementation and (4) dyad model adoption and model fidelity. Research limitations/implications: Research in this area remains nascent, and most articles focused on implementation over evaluation. It is possible that some articles were excluded due to our methodology, which excluded nonEnglish articles. Practical implications: Findings provide guidance for health care organizations seeking to implement dyadic leadership models. Rigorous studies are needed to establish the impact of dyadic leadership models on quality and patient outcomes. Originality/value: This review consolidates evidence surrounding the implementation and evaluation of a leadership model gaining prominence in health care.